2009
DOI: 10.1262/jrd.20241
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Enter Rat Ovarian Granulosa Cells and Subcellular Organelles, and Alter <i>In-Vitro</i> Estrogen Accumulation

Abstract: Abstract. Nanoparticle technology refers to research and technology developed at the atomic or molecular level for materials of approximately 1-100 nm in length. Through accidental or involuntary exposure, nanoparticles are potentially toxic to the body, including reproductive organs. Ovarian granulosa cells play a major role in maintaining ovarian function, health, and female fertility. Since these cells are involved in steroidogenesis, we wished to evaluate whether nanoparticles affected them after traversin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 35 publications
(42 reference statements)
1
57
2
Order By: Relevance
“…25 In addition, gold NPs can enter Chinese hamster ovary cells through the endocytic pathway, 26 infiltrate rat ovarian granulosa cells and subcellular organelles, and alter in vitro estrogen accumulation. 27 Moreover, mitogen-activated protein kinase cellular signal transduction pathways in mammalian cells can be activated by silicon carbide nanowires. 28 Furthermore, evidence has shown that chronic exposure of Enchytraeus albidus worms to Cu NPs results in lower reproductive output compared to exposure to CuCl 2 salt.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, gold NPs can enter Chinese hamster ovary cells through the endocytic pathway, 26 infiltrate rat ovarian granulosa cells and subcellular organelles, and alter in vitro estrogen accumulation. 27 Moreover, mitogen-activated protein kinase cellular signal transduction pathways in mammalian cells can be activated by silicon carbide nanowires. 28 Furthermore, evidence has shown that chronic exposure of Enchytraeus albidus worms to Cu NPs results in lower reproductive output compared to exposure to CuCl 2 salt.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the toxicologic characteristics of some nanomaterials in ovarian cells in vitro have been reported. For instance, gold nanoparticles were shown to enter rat ovarian granulosa cells and subcellular organelles and alter estrogen accumulation in vitro [23], and were able to traverse the cell membrane and enter Chinese hamster ovary cells by the endocytic pathway [24]. In addition, calcium phosphate nanoparticles entered granulosa cells, and were distributed in the membranous compartments, including lysosome, mitochondria and intracellular vesicles, affected hormone production, and caused apoptosis in human granulosa cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators studied specific nanoparticle interactions with single cellular system in which parameters can be controlled, even though this type of model is artificial. Up to date, no consensus exist in regard with the subcellular location of AuNPs (reviewed in Khlebtsov and Dykman [17]): freely dispersed in cytoplasm [18][19][20] clustered in vesicles [7,11,12,18,21,22]. Some studies showed a high fraction of radioactive AuNPs linked to DNA [23], an aggregation of small AuNPs (2 nm) within the nuclei which were damaged [24], a nuclear fragmentation [25,26].…”
Section: Introductionmentioning
confidence: 99%